Metody naukowe stosowane w ramach wykładu z przedmiotu Historia administracji - Kruszewski, Tomasz (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
The author presents the organization of lectures prepared for the course History of Administration, delivered to first-year students of bachelor (undergraduate) studies in administration. The subject matter of the lectures joins the histories of executive power in Poland and European models. The lectures cover the period between the Middle Ages and the end of WWII. The students familiarize themselves with the content of the lectures by participating in the classes and lectures, and by reading the prescribed course book and source texts.
Keywords: historia administracji; Polska; Europa; periodyzacja; metody naukowe; historia państwa i prawa